Hand Sanitizer Gel Formulations Oil StocksEssential Pala ( Myristica Fragrans Houtt . ) : Stability TestPhysical Activity And Test Against AntibacterialStaphylococcus Aureus Bacteria - Octavia, Nurlina; , Arifah Sri Wahyuni. M.Sc., Apt (2016)
Nutmeg oil (Myristica fragrans Houtt.) with a content myristicin has antibacterial activity against Staphylococcus aureus so suitable for use as an active ingredient in the preparation of gel hand sanitizer. This study aims to determine the effect of variations in the concentration of carbopol as gelling agent on the physical properties and the physical stability during storage and determine the antibacterial activity of essential oils of nutmeg against Staphylococcus aureus after formulated in gel form. Gel hand sanitizer made with carbopol variation concentration of 0,5%; 1%; 1,25%; and 1,5% w/v. Evaluation of hand sanitizer gel preparations include organoleptic, pH, viscosity, dispersive power, and adhesion as well as antibacterial activity test against Staphylococcus aureus. Data of phtsical properties were analyzed with Kruskal Wallis, if p <0.05 then analyzed by Mann Whitney. Data of physical stability and inhibition zone analyzed by Multivariate. The results show that the variation concentration of carbopol affect the physical properties and physical stability during storage. Increasing concentrations of carbopol used, can lower the pH and dispersive power, as well as to increase the viscosity and adhesiveness of the preparation. All formulas have poor stability during storage. Nutmeg essential oil still possess antibacterial activity against Staphylococcus aureus after formulated in a gel hand sanitizer.